The pediatric emergency department care experience: A quality measure - Terri Byczkowski; Kimberly Downing; Michael FitzGerald; Stephanie Kennebeck; Gordon Gillespie; Evaline Alessandrini (The Beryl Institute, 2018)
To develop and validate a measure of the quality of the pediatric emergency department care experience from the parent perspective. This was a multiphase study conducted at a tertiary-care pediatric health system using qualitative and quantitative methods. A list of candidate questions was developed to measure each of eight dimensions of family-centered pediatric emergency care described in a published framework. This list was evaluated and refined using the Question Appraisal System (QAS-99) followed by cognitive interviewing methods. Remaining questions were field tested using survey methods via telephone interviews with randomly selected parents. Composite scores to measure each of the eight dimensions of family-centered pediatric emergency care were calculated. Reliability was evaluated using measures of internal consistency. Construct validity was evaluated by measuring the association of each question and composite scores with overall satisfaction. A pool of 77 questions was reduced to 51 using QAS-99 criteria. Cognitive interviews with 19 parents resulted in a final list of 24 questions for field testing. With a response rate of 46%, 404 parents participated in the field test. Each individual question exhibited a significant positive association with overall satisfaction. Measures of internal consistency did not support the composite scores based on the initial eight dimensions. An exploratory factor analysis resulted in alternative composite measures that exhibited acceptable reliability and construct validity. This study has resulted in a measure that can be used to inform quality improvement work aimed at improving the pediatric emergency department care experience.